Pengaruh Pajak, Mekanisme Bonus Dan Exchange Rate Terhadap Keputusan Untuk Melakukan Transfer Pricing: (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2016-2020) - Esa Agustin; Hari Stiawan (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This research aims to provide empirical evidence of the influence of taxes, bonus mechanisms, and exchange rates on transfer pricing decisions. This study used a sample of manufacturing companies listed on the Indonesia Stock Exchange during the period 2016 to 2020. The number of companies sampled by this study was 11 sampling, the total sample of this study was 55 units of analysis. The type of research used is quantitative research. The study used purposive sampling. The data analysis in this study used regression using Eviews version 9 software. The results of this study show that taxes, bonus mechanisms, exchange rates together have an simultaneous effect on the decision to transfer pricing. Partial testing concluded that taxes had no effect on transfer pricing, bonus mechanisms had no effect on transfer pricing, and exchange rates had an effect transfer pricing.